Penerapan Alat Peraga Mistar Hitung Bilangan Bulat Untuk Meningkatkan Kemampuan Berhitung Siswa Sekolah Luar Biasa Negeri Kanatang - Elsy Senides Hana Taunu; Yuliana Tamu Ina Nuhamara (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study was to find out how the use of slide rule media can improve students' numeracy skills in integer arithmetic operations for Kanatang State Special School students. This Classroom Action Research (PTK) was conducted at the Kanatang Foreign School in the Odd Semester of the 2022/2023 academic year. The subjects in this study were the students of the Kanatang State Special School, which consisted of 10 students, namely 5 students and 5 female students. The research object is the Ruler Count media in learning addition and subtraction of integers in Mathematics. The procedures/steps of this Classroom Action Research consist of cycles. Implementation of this Classroom Action Research each cycle includes: planning, implementation of action, observation, and reflection. The instruments used in this study were pre-test questions, post-test questions for each cycle, and interview guidelines. The questions made consist of 10 numbers in the form of an essay test. The data collection technique used was the provision of tests, interviews, observations and field notes. The instrument used is a test in the form of a description. Data collection was carried out in three stages, namely: (1) reducing data, (2) presenting data, and (3) drawing conclusions. The results showed that student activities and teacher activities in learning activities in cycle I reached the Good category and cycle II was very good. The results of the analysis of the final test cycle I obtained the percentage of average scores with student absorption reaching 60% and learning completeness reaching a percentage 70% of 10 students. Whereas in the analysis of the final test cycle II there was an increase according to the results of observations of student and teacher activities, the percentage of the average value of student absorption reached 90% with classical learning completeness reaching the target percentage of 100% of 10 students. This has shown that there is an increase in the learning outcomes of Kanatang State Special School students in the material of addition and subtraction of integers by using the integer slide rule.